Multiomic analysis reveals microbiome-related relationships between cocaine use and metabolites. (1st December 2022) - Martinez, Sabrina Sales; Stebliankin, Vitalii; Hernandez, Jacqueline; Martin, Haley; Tamargo, Javier; Rodriguez, Jose Bastida; Teeman, Colby; Johnson, Angelique; Seminario, Leslie; Campa, Adriana; Narasimhan, Giri; Baum, Marianna K.
Abstract : Objective: Over 19 million individuals globally have a cocaine use disorder, a significant public health crisis. Cocaine has also been associated with a pro-inflammatory state and recently with imbalances in the intestinal microbiota as compared to nonuse. The objective of this pilot study was to characterize the gut microbiota and plasma metabolites in people with HIV (PWH) who use cocaine compared with those who do not. Design: Cross-sectional study. Methods: A pilot study in PWH was conducted on 25 cocaine users and 25 cocaine nonusers from the Miami Adult Studies on HIV cohort. Stool samples and blood plasma were collected. Bacterial composition was characterized using 16S rRNA sequencing. Metabolomics in plasma were determined using gas and liquid chromatography/mass spectrometry. Results: The relative abundances of the Lachnopspira genus, Oscillospira genus, Bifidobacterium adolescentis species, and Euryarchaeota phylum were significantly higher in the cocaine- using PWH compared to cocaine-nonusing PWH. Cocaine-use was associated with higher levels of several metabolites: products of dopamine catabolism (3-methoxytyrosine and 3-methoxytyramine sulfate), phenylacetate, benzoate, butyrate, and butyrylglycine. Conclusions: Cocaine use was associated with higher abundances of taxa and metabolites known to be associated with pathogenic states that include gastrointestinal conditions. Understanding key intestinal bacterial functional pathways that are altered due to cocaine use in PWH will provide a better understanding of the relationships between the host intestinal microbiome and potentially provide novel treatments to improve health.